Developing Arithmetic Competence in Primary Learners with the Aid of Educational Technology - Ledesma, Elena Fabiola Ruiz; Báez, Lorena Chavarría; González, Alan Isaac Trinidad (Journal of Cultural Analysis and Social Change, 2025)
The development of math skills is crucial from an early age because it helps children enhance their ability to calculate, estimate, understand, and work with numbers, as well as solve math problems. It also lays a key foundation for developing critical thinking and problem-solving skills. Due to its importance, a research project was conducted to reinforce arithmetic knowledge and strengthen the development of numerical, operational, and systematic skills that students need from early education onward. As part of this effort, an educational application was created and launched—a mobile app featuring four video games: Little Races, Mischievous Spirits, Chocolaty, and Make Your Pizzas—designed for elementary school students. The app enables them to practice arithmetic operations with whole numbers and decimals, work with fractions, and find equivalent fractions. The interactive design encourages engagement with the topics presented in each game. This article describes the development and implementation of the software, as well as its evaluation with 189 elementary school students over two months as part of their school activities. Using Bonferroni's post hoc test, significant differences were observed in several comparisons between the games. Little Races scored significantly higher than Chocolaty (p = .013), Make Your Pizzas (p < .001), and Mischievous Spirits (p = .039), consistently receiving higher ratings.